THE ROLE OF INTERNATIONAL LAW IN PREVENTING AND ADDRESSING HUMAN TRAFFICKING FROM THE PERSPECTIVE OF THE RIGHT TO PRIVACY UNDER ICCPR - Ida Bagus Mahendra Praditama; Ida Bagus Erwin Ranawijaya (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
This research aims to explore the regulations and principles of human rights and the role of International Law in preventing and addressing trafficking in persons, with a specific focus on the Right to Privacy outlined in the International Covenant on Civil and Political Rights (ICCPR). Furthermore, the study seeks to analyze the contribution of International Law to combat trafficking in persons from an ICCPR perspective. The act of trafficking violates various principles of international human rights, including the Right to Privacy as stipulated in Article 17 of the ICCPR. However, Article 17 also acknowledges that the right to privacy may be limited in cases of public interest or to safeguard the rights of others. The challenge lies in determining appropriate limitations on the right to privacy in specific situations, leading to norm vagueness. This research adopts a normative legal research method, incorporating a statutory approach relevant to the legal domain under examination, as well as conceptual and analytical approaches. The findings revealed that effective international cooperation is crucial in combating human trafficking. Nations must ensure that their domestic laws align with international legal standards for prevention and intervention in human trafficking. Adoption and implementation of pertinent international instruments such as the Palermo Protocol, an adjunct to the UN Convention against Transnational Organized Crime, and the Protocol on Combating Trafficking in Persons are recommended for this purpose.